The Potential of Liquid Organic Fertilizer for Hydroponic Nutrition: A Systematic Literature Review - Syamsia, Syamsia (Journal of Agriculture, 2024)
Nutrients are the main component in a hydroponic system. Liquid organic fertilizer has the potential to be a source of hydroponic nutrition because it can be made from agricultural waste through a fermentation process using local microorganisms. The aim of the research is to analyze articles that use the theme of liquid organic fertilizer and describe various topics that are relevant and have novelties to be developed in future research. The bibiometric analysis used in the research used the 2019-2023 literature. The data collection method uses dimensions with the keyword "liquid organic fertilizer" to obtain 500 papers published in 2019-2023. The data was sorted into 300 articles for further analysis with the help of VOSviewer 1.6.19_Mac software. The research results show that the theme of liquid organic fertilizer implemented in scientific articles has become a serious concern and has had high interest value for researchers over the last 4 years. Several new topics that need to be studied further to support the development of liquid organic fertilizer as nutrition in hydroponic systems to support sustainable agriculture include: local microorganisms (mol), biostimulants, cocopeat, chicken manure. Elsevier is a publisher in the main ranking which publishes articles and is widely cited. Keywords with different topics are needed to analyze articles to get new ideas and innovations in developing knowledge and technology that supports sustainable agriculture.